Prevalence of Giardia duodenalis infection, co-morbidities and associated risk factors in dogs admitted to a veterinary teaching hospital in Israel. (February 2020) - Kuzi, Sharon; Eshcol Argentaro, Sigal; Baneth, Gad
Highlights: Giardia duodenalis prevalence in dogs presented to a hospital in Israel was 11.7%, relatively low compared to reports from other countries. G. duodenalis infection was associated with young age, but not with kennel housing or presence of clinical signs. Canine Parvovirus infection was associated with G. duodenalis . Other infectious intestinal diseases approached a significant association. Other inflammatory GI diseases, pancreatic and systemic diseases were unassociated with G. duodenalis infection. Abstract: Giardia duodenalis causes gastro-intestinal (GI) disease and carries a zoonotic risk. The risk for infection depends on local prevalence and individual immunity, but clinical signs are inconsistent and the role of G. duodenalis in other GI diseases is unknown. The current study aims were to evaluate the prevalence of G. duodenalis in dogs presented to a university veterinary teaching hospital in Israel, investigate risk factors for infection and its associations with other diseases. Fecal samples from 163 dogs were tested for G. duodenalis by an antigen assay (FASTest® Giardia strip). Prevalence of G. duodenalis infection was 11.9 %. It was significantly associated with young age (≤1year) and canine parvoviral enteritis. Housing conditions, signs of GI disease or other systemic diseases were unassociated with infection. In conclusion, G. duodenalis infection prevalence is relatively low in the study population. Young age and diagnosis of co-infections are common, warranting screening for G. duodenalis .